انعكاس حوكمة الشركات على جودة التقارير المالية في المؤسسة الإقتصادية الجزائرية شركة اليانس للتأمينات الجزائرية لفترة (2018-2019) - ليله, ياسين; مكاوي, فريد; قريشة, عثمان (University of eloued جامعة الوادي, 2019)
"تحظى حوكمة الشركات بإهتمام كبير من قبل الشركات العالمية الرائدة في مجال الأعمال، خاصة بعد الأزمات المالية الحالية، وما نتج عنها من ضرر لمبدأ الثقة، هذا الأخير كان حلا مناسبا لقبول فكرة الحوكمة، بهدف زيادة المساءلة والمصداقية وكذا الشفافية في الإفصاح؛ وتهدف هذه الدراسة إلى إبراز إنعكاس حوكمة الشركات علي جودة التقارير المالية في الشركات الجزائرية، من خلال تطبيق جملة من مبادئ وآليات الخاصة بحوكمة الشركات بالشكل السليم والفعّال، لعل أهمها المراجعة الداخلية ومجلس الإدارة، لجنة المراجعة والمراجعة الخارجية، ذلك كي تؤدي الغرض المرجو منها، ألا وهو جودة المعلومات امحاتوة في التقارير المالية، والتي تعد عاملا أساسيا في إتخاذ القرارات لمستخدميها، وتنعكس بدورها في تنشيط حركة سوق الأوراق المالية وعليه توليد القيمة الحقيقة للشركة من خلال التطبيق الجيد للحوكمة خاصة علي مستوي بيئة الأعمال الجزائرية. وفي ضوء طبيعة هذه الدراسة والأهداف التي تسعى إلى تحقيقها، تم إستخدام المنهج الوصفي التحليلي معتمدين في ذلك على أسلوب الإستبانة الذي تم توزيعه على مجتمع الدراسة المكون من موظفي شركة أليانس للتأمينات الجزائرية، وخلصت الدراسة إلى وجود إنعكاس إيجابي ذا علاقة قوية، بين الحوكمة وجودة التقارير المالية في الشركة حلل الدراسة. "Corporate government is highly regarded by leading global business firms, especially after the current financial crisis, resulting in damage to the principal of trust. The latter was an appropriate solution to accept the idea of government in order to increase accountability, credibility and transparency in disclosure, the study aims to highlight the reflection of corporate government on the quality of financial report in Algerian companies through applying sum of principles and mechanisms for corporate government in correct and effective manner, most important; the internal audit, the board of Directors, audit Committee and external audit, in order to achieve the desired purpose, which is the quality of the information contained in the financial reports, and it is the main factor in the decision making for users, and is reflected to stimulate the movement of the stock market, so generating the real value of the company through the good application of government, especially at the level of Algerian business environment. In the light of the nature of this study and the objective it aims to achieve, the analytical descriptive approach was used, relying on the questionnaire method that was distributed to the study community composed of the staff of ALLIANCE insurance company. The study concluded that there is a strong positive correlation between government and the quality of financial reports in the company under study.
مذكرة ماستر محاسبة
Keywords: حوكمة الشركات، جودة التقارير المالية، المؤسسات الاقتصادية الجزائرية.; corporate government, quality of financial reports, Algerian economic